Impact of supply chain management on Customer Loyalty to the ‘Aarong’ Fashion House Brand - Dewan Golam Yazdani Showrav; Dr. Mohammed Masum Iqbal; Tamanna Sharmin Chowdhury (International Journal of Supply Chain Management, 2020)
Abstract- Achieving and retaining Customer loyalty is important objective for any business. Supply Chain Management synchronizes the efforts of all parties-particularly suppliers, manufacturers, retailers, dealers, customers-involved in achieving customer's needs. Customer satisfaction, retention rates, and the customer loyalty positively influence the performance of the business and assist to achieve competitive gain. Fashion house brands in Bangladesh are growing with developing some exclusive brands. Aarong is one of the prestigious and recognized brands in apparel industry of Bangladesh. The purpose of this research is to examine the factors that determine customer loyalty towards Aarong. In this research, ‘loyalty’ means customer perception about the brand and repurchase intention from Aarong.  Independent Variables (factors) were chosen after interviewing customers with buying experience from Aarong, and previous studies on fashion industry. A non-probability judgmental sampling methodology was followed for primary data collection and 301 completed sample responses were collected. Descriptive statistics were conducted to describe the demographic information of the respondents; twelve factors were tested to find out their influence on customer loyalty toward Aarong.  Principal Component Factor analysis was used to reduce the less significant factors and find the high significant factors. After data analysis it is found that three major factors labeled as customer perception about the brand, customers’ economic benefits and shopping environment. From these factors, the first factor which is customer perception about the brand found most significant factor to explain customer loyalty toward Aarong. These result might help Aarong to better segment the market and to create more effective marketing program. It may also give a guideline to other brands in the same industry and might be important literature for future researchers in apparel sector.